2003
DOI: 10.1038/pcrj.2003.65
|View full text |Cite
|
Sign up to set email alerts
|

Continuing medical education for asthma in primary care settings: a review of randomised controlled trials

Abstract: Background: The aim of this paper is to review evidence of the effectiveness of educational interventions for General Practitioners for health outcomes of patients with asthma. Methods:The 'Research and Development Resource Base in CME' was searched in addition to searches of the Cochrane, Medline, CINAHL and ERIC databases for original articles published between 1966 and October 2002. Inclusion criteria for the studies were that, the study was a randomised controlled trial (RCT), that the intervention include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…24 Rigorous evaluation of standardised educational interventions are uncommon, 25 and a systematic review of the effectiveness of continuing medical education (principally small group interactive seminars for general practitioners) in improving outcomes for patients with asthma was inconclusive. 26 In contrast, a recent trial has shown that multifaceted educational programmes (or 'blended learning') which is sensitive to local circumstances and designed to build clinicians' sense of importance about change ('why') as well as their confidence to achieve change ('how') can reduce antibiotic prescriptions in primary care. 27 …”
Section: Education and Continuing Medical Educationmentioning
confidence: 99%
“…24 Rigorous evaluation of standardised educational interventions are uncommon, 25 and a systematic review of the effectiveness of continuing medical education (principally small group interactive seminars for general practitioners) in improving outcomes for patients with asthma was inconclusive. 26 In contrast, a recent trial has shown that multifaceted educational programmes (or 'blended learning') which is sensitive to local circumstances and designed to build clinicians' sense of importance about change ('why') as well as their confidence to achieve change ('how') can reduce antibiotic prescriptions in primary care. 27 …”
Section: Education and Continuing Medical Educationmentioning
confidence: 99%
“…Barton et al, in their systematic review [6] on the effectiveness of Continuing Medical Education (CME) for improving health outcomes of patients with asthma, were unable to make firm recommendations. This paper prompted us to commission an editorial by Monica Fletcher (Chief Executive of the National Respiratory Training Centre, Warwick, UK) [7].…”
Section: What's In This Issue?mentioning
confidence: 99%